Stretch‐induced helix to extended coil transition of crystalline α phase isotactic polypropylene: A molecular dynamics study. Issue 4 (30th July 2020) - Pal, Subhadeep; Mitra, Nilanjan; Sarkar, Prodip Kumar; Prasad, Dipak
Abstract: Stretch induced helix to extended coil transition is studied in crystalline α phase of isotactic polypropylene with full atom molecular dynamics simulation during a uniaxial stretching process using a reactive potential. The transition is observed prior to the breaking of the main carbon chain. The mechanism of this transition is identified based on dihedral angle evolution, helix radius, and pitch length evolution along with the evolution of methyl vector rotation. Additionally, it is observed that the helix to coil transition occurs much faster (at comparatively lower strains) for higher temperatures (lower than melting temperature) compared to ambient temperature. Abstract : The helix to extended coil transition is studied in crystalline α‐iPP with full atom molecular dynamics simulations during the uniaxial stretching process using a reactive potential. The transition is observed prior to the breaking of the backbone carbon chain and identified based on the evolution of dihedral angle distribution, helix radius, and pitch length. At the higher temperature (lower than T m ), the transition occurs at lower strain compared to ambient temperature.